Neoadjuvant immune checkpoint blockade in high-risk resectable melanoma. (November 2018) - Amaria, Rodabe; Reddy, Sangeetha; Tawbi, Hussein; Davies, Michael; Ross, Merrick; Glitza, Isabella; Cormier, Janice; Lewis, Carol; Hwu, Wen-Jen; Hanna, Ehab; Diab, Adi; Wong, Michael; et al.
Abstract Preclinical studies suggest that treatment with neoadjuvant immune checkpoint blockade is associated with enhanced survival and antigen-specific T cell responses compared with adjuvant treatment1 ; however, optimal regimens have not been defined. Here we report results from a randomized phase 2 study of neoadjuvant nivolumab versus combined ipilimumab with nivolumab in 23 patients with high-risk resectable melanoma (NCT02519322 ). RECIST overall response rates (ORR), pathologic complete response rates (pCR), treatment-related adverse events (trAEs) and immune correlates of response were assessed. Treatment with combined ipilimumab and nivolumab yielded high response rates (RECIST ORR 73%, pCR 45%) but substantial toxicity (73% grade 3 trAEs), whereas treatment with nivolumab monotherapy yielded modest responses (ORR 25%, pCR 25%) and low toxicity (8% grade 3 trAEs). Immune correlates of response were identified, demonstrating higher lymphoid infiltrates in responders to both therapies and a more clonal and diverse T cell infiltrate in responders to nivolumab monotherapy. These results describe the feasibility of neoadjuvant immune checkpoint blockade in melanoma and emphasize the need for additional studies to optimize treatment regimens and to validate putative biomarkers. Neoadjuvant combination treatment with nivolumab and ipilimumab in patients with high-risk melanoma results in higher response rates than nivolumab monotherapy and warrants future optimization of dosing regimens to preserve efficacy while limiting toxicity.